PENGARUH APLIKASI MIKORIZA, TRICHODERMA SP DAN PUPUK NPK TERHADAP PENYAKIT LAYU FUSARIUM SERTA HASIL BAWANG MERAH DI MEDIA GAMBUT - Y., E, Silalahi,; R., B., Mulyani,; S., Winarti (AgriPeat, 2020)
The purpose of this research is to find out the effect of mycorrhizae, Trichoderma sp. and NPK fertilizer application to control Fusarium wilt diseases and to increase onion yield in peat soil media. This research was used a completely randomized factorial design (RAL) consisting of two factors with three replications. The first factor is application of biological agents (a) consists of: a0 = No biological agents, without pathogens; a1=No biological agents, pathogen inoculation; a2 = mycorrhizae 15 g; a3 = Trichoderma sp. 20 g; a4 = Mycorrhizal 10 g + Trichoderma sp. 10 g. The second factor is NPK fertilizer dosage (p) consists of: p0 = without treatment; p1 = NPK 300 kg ha-1; p2 = NPK 200 kg ha-1; p3 = NPK 150 kg ha-1. Observations included i) Fusarium wilt intensity, ii) effectiveness of control, iii) plant height, iv) tuber wet weight, v) tuber dry weight, and vi) mycorhizal root colonization. The results showed that a single application of 15 g mycorrhiza, Trichoderma sp. 20 g and mycorrhizal consortium and Trichoderma sp. with a dose of each 10 g and NPK fertilizer was able to suppress the Fusarium wilt disease with a control effectiveness of 83.27% and increase the onion yield at the age of 5 week after inoculation with an increase in plant height of 52.09 cm. Mycorrhizal dosage of 15 g plant-1 can increase the fresh weight of tubers per clump weighting 37.31 g, and increase the dry weight of tubers per clump weighting 28.81 g in peat soil medium